Monitoring the morphological evolution in mixed-dimensional lead bromide perovskite films with lamellar-stacked perovskite nanoplatelets. Issue 5 (1st May 2019) - Wang, Rui; Tong, Yu; Wang, Kun; Xia, Senlin; Kentzinger, Emmanuel; Soltwedel, Olaf; Müller-Buschbaum, Peter; Frielinghaus, Henrich
Abstract : The formation of 3D lead bromide perovskite crystals and the self-assembly of lamellar-stacked 2D perovskite nanoplatelets are comprehensively studied. Abstract : Mixed-dimensional lead bromide perovskite films combine the properties of both three-dimensional (3D) and two-dimensional (2D) perovskite crystals, and due to their good humidity tolerance, they emerge as promising candidates for long-term stable optoelectronic applications. In order to further tailor the film morphology aiming for a better device performance, it is important to unravel the structural formation mechanism in these perovskite thin films. In the present study, the formation of 3D lead bromide perovskite crystals and the self-assembly of lamellar-stacked 2D perovskite nanoplatelets are comprehensively studied. Samples are prepared through a two-step vapor assisted route with different vapor exposure times in order to monitor the detailed morphology at the specific reaction stage. With grazing incidence X-ray scattering techniques, the preferential orientation of the 3D crystals is found to decrease upon increasing the reaction time. Also, it is evidenced that well-ordered in-plane lamellar-stacked 2D nanoplatelets form aggregates in the bulk structure only. The obtained hierarchical morphology shows excellent structural stability in a humid atmosphere even at a relative humidity level of 80%. Our findings statistically offer a morphological understanding, which is important for the optimization of the sample preparation route and thus the resulting performance of moisture-tolerant perovskite based optoelectronic devices.